2022
DOI: 10.3390/microorganisms10061129
|View full text |Cite
|
Sign up to set email alerts
|

Tooth-Specific Streptococcus mutans Distribution and Associated Microbiome

Abstract: Dental caries is multifactorial and polymicrobial in nature and remains one of the most common oral diseases. While caries research has focused on Streptococcus mutans as the main etiological pathogen, its impact at the tooth level is not fully understood. In this cross-sectional study, the levels and distribution of S. mutans in the posterior teeth at different dentition stages were investigated along with the corresponding tooth-specific microbiome. Occlusal plaque samples of 87 individual posterior teeth we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 58 publications
0
1
0
1
Order By: Relevance
“…Meanwhile, according to the relative abundance of microbial phenotypes, an increase in Neisseria was present at both ages and positively influenced the respective potential pathogen phenotypes. Neisseria, classified in the phylum Proteobacteria, is a prevalent microbe seen in early childhood caries (ECC) (Xu et al, 2023) and is crucial in the progression of dental caries (Dinis et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, according to the relative abundance of microbial phenotypes, an increase in Neisseria was present at both ages and positively influenced the respective potential pathogen phenotypes. Neisseria, classified in the phylum Proteobacteria, is a prevalent microbe seen in early childhood caries (ECC) (Xu et al, 2023) and is crucial in the progression of dental caries (Dinis et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…En salud pública su importancia se debe a la prevalencia, el impacto individual y social, y los costos para su tratamiento una vez instaurado el problema (2) Aunque las biopelículas dentales son complejas y consisten en diversas comunidades microbianas, el Streptococcus mutans es considerado como el principal patógeno en el inicio y desarrollo de la caries dental (3). Si bien otras especies pueden desempeñar un papel en el inicio y progresión de la caries dental, las investigaciones han establecido al Streptococcus mutans como un patógeno cariogénico primario (4) Se debe reconocer la importancia del uso de las plantas en la vida del ser humano, quienes han recurrido a estas como fuente de medicación y salud (5). Las plantas son un recurso valioso en los sistemas de salud de los países en desarrollo.…”
Section: Introduccionunclassified
“…In recent years, high-throughput sequencing has been used to study caries-associated microorganisms, and the sequencing results of the key oral bacteria for dental caries are often inconsistent. It has been found that S. mutans is not the dominant bacterium in plaque biofilm, as it is present at a low level in some caries patients and can also be detected in caries-free individuals ( Dinis et al, 2022 ). Thus, other bacteria must be involved in the process of caries development.…”
Section: Introductionmentioning
confidence: 99%